Attachment, Entry, and Intracellular Trafficking of Classical Swine Fever Virus - Xin Guo; Maolin Zhang; Xiaomin Liu; Yannan Zhang; Chongyang Wang; Yidi Guo (Viruses, 2023)
Classical swine fever virus (CSFV), which is a positive-sense, single-stranded RNA virus with an envelope, is a member of the Pestivirus genus in the Flaviviridae family. CSFV causes a severe and highly contagious disease in pigs and is prevalent worldwide, threatening the pig farming industry. The detailed mechanisms of the CSFV life cycle have been reported, but are still limited. Some receptors and attachment factors of CSFV, including heparan sulfate (HS), laminin receptor (LamR), complement regulatory protein (CD46), MER tyrosine kinase (MERTK), disintegrin, and metalloproteinase domain-containing protein 17 (ADAM17), were identified. After attachment, CSFV internalizes via clathrin-mediated endocytosis (CME) and/or caveolae/raft-dependent endocytosis (CavME). After internalization, CSFV moves to early and late endosomes before uncoating. During this period, intracellular trafficking of CSFV relies on components of the endosomal sorting complex required for transport (ESCRT) and Rab proteins in the endosome dynamics, with a dependence on the cytoskeleton network. This review summarizes the data on the mechanisms of CSFV attachment, internalization pathways, and intracellular trafficking, and provides a general view of the early events in the CSFV life cycle.